Antibacterial, Cytotoxic Studies and Characterization of Some Newly Synthesized Symmetrical N3, N3′-Bis(disubstituted)isophthalyl-bis(thioureas) and Their Cu(II) and Ni(II) Complexes. (23rd December 2013) - Jamil, Muhammad; Zubair, Muhammad; Asim Farid, Muhammad; Rashid, Umer; Rasool, Nasir; Islam, Saiful
Abstract : A series of some novel N 3, N 3 ′ -bis(disubstituted)isophthalyl-bis(thioureas) compounds with general formula [C6 H4 · CONHCSNHR2 ], where R = 2-ClC6 H4 S (L 1 ), 3, 5-(Cl)2 C6 H3 (L 2 ), 2, 4-(Cl)2 C6 H3 (L 3 ), 2, 5-(Cl)2 C6 H3 (L 4 ), and 2-NH2 C6 H4 (L 5 ), and their Cu(II) and Ni(II) complexes (C 1 –C 10 ) have been synthesized. These compounds (L 1 –L 5 ) and their metal(II) complexes (C 1 –C 10 ) have been characterized by elemental analysis, infrared spectroscopy, 1 H NMR and 13 C NMR spectroscopy, magnetic moments, and electronic spectral measurements. The ligands are coordinated to metal atom in a bidentate pattern producing a neutral complex of the type [ML]2 . These compounds (L 1 –L 5 ) and their metal(II) complexes (C 1 –C 10 ) were also screened for their antibacterial and cytotoxic activities.